Combined Local and Systemic Ozone Therapy in the Treatment of the Low Back Pain: A Proposed Protocol and a Suggested Mechanism of Action - Emma Borrelli (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
In recent decades the paravertebral injection of an oxygen-ozone gas mixture in paravertebral muscles for the treatment of the low back pain has undergone a remarkable development worldwide. In fact, ozone has great antalgic properties and after a limited number of injections the patient feels often an improvement in symptoms. However, long-term data on ozone efficacy are poor and patients may experience a relapse in low back pain. In this chapter, a combined method using local and systemic ozone therapy will be described in order to associate a rapid symptomatologic improvement with a sustained long-term efficacy during the treatment of this diffused musculoskeletal disease.